2005
DOI: 10.1590/s0034-70942005000600011
|View full text |Cite
|
Sign up to set email alerts
|

O Bloqueio do plexo hipogástrico superior é eficaz no tratamento de dor pélvica crônica?

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…In this context, the superior hypogastric plexus is considered an ideal target for nerve blocking to reduce pelvic visceral pain, [6] and it has been blocked to relieve both benign and malignant pain affecting the pelvic visceral structures. [610] …”
Section: Discussionmentioning
confidence: 99%
“…In this context, the superior hypogastric plexus is considered an ideal target for nerve blocking to reduce pelvic visceral pain, [6] and it has been blocked to relieve both benign and malignant pain affecting the pelvic visceral structures. [610] …”
Section: Discussionmentioning
confidence: 99%
“…The afferent fibers innervating the pelvic viscera (the bladder, uterus, vagina, prostate, testes, urethra, descending colon, and rectum) travel with sympathetic nerves, ganglia, superior hypogastric plexus (SHP), and therefore are amenable to percutaneous NSHB. [ 7 64 65 ] The SHP is a retroperitoneal structure located bilaterally from L3 to upper third of S1, close to sacral promontory and common iliac veins bifurcation. [ 7 64 ] Schmidt et al , reviewed the available literature and found NSHB to be safe and effective.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%
“…[ 7 64 65 ] The SHP is a retroperitoneal structure located bilaterally from L3 to upper third of S1, close to sacral promontory and common iliac veins bifurcation. [ 7 64 ] Schmidt et al , reviewed the available literature and found NSHB to be safe and effective. [ 64 ] Mishra et al , in a recently conducted RCT reported NSHB to be superior to oral morphine with respect to pain score reduction, improvement in functional capacity, and global satisfaction score.…”
Section: Interventional Pain Management Guidelines According To Clinimentioning
confidence: 99%
See 1 more Smart Citation
“…No que tange ao bloqueio anestésico dos nervos do plexo lombossacral, os trabalhos utilizam o homem como fonte de estudo (Schmidt et al 2005, Zugliani et al 2007, Imbelloni 2008.…”
Section: Introductionunclassified